Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702498
|View full text |Cite
|
Sign up to set email alerts
|

Improving Multilingual Collaboration by Displaying How Non-native Speakers Use Automated Transcripts and Bilingual Dictionaries

Abstract: Conversational grounding, or establishing mutual knowledge that messages have been understood as intended, can be difficult to achieve when some conversational participants are using a non-native language. These difficulties in grounding can be challenging for native speakers to detect. In this paper, we examine the value of signaling potential grounding problems to native speakers (NS) by displaying how non-native speakers (NNS) use automated transcripts and bilingual dictionaries. We conducted a laboratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We used them as a base because they also focus on the listening comprehension problems of NNSs that occur during their cognitive processing of speech input. Note that we added a new category "lack of vocabulary" to the previous categories [8], [11] because it can be solved by adding a dictionary function to the ASR transcripts [12]. All the interview data were coded independently by two coders, and all discrepancies were discussed until an agreement was reached.…”
Section: Resultsmentioning
confidence: 99%
“…We used them as a base because they also focus on the listening comprehension problems of NNSs that occur during their cognitive processing of speech input. Note that we added a new category "lack of vocabulary" to the previous categories [8], [11] because it can be solved by adding a dictionary function to the ASR transcripts [12]. All the interview data were coded independently by two coders, and all discrepancies were discussed until an agreement was reached.…”
Section: Resultsmentioning
confidence: 99%
“…Duan and colleagues [13] employed an intelligent agent that asked clarification questions so that NS were aware of potential confusions that NNS may be too shy to acknowledge. Gao et al [19] provided NS with a shared display of how their NNS teammates were using real-time transcripts and a bilingual dictionary and found that this increased NS's awareness of the specific difficulties NNS were experiencing. Still, these tools engaged NS only at the awareness level.…”
Section: Challenges In Multiparty Communication Between Ns and Nnsmentioning
confidence: 99%
“…No significant effect of trial (F [1, 38] = 1.75, p = . 19) and no interaction (F [1, 38] = 1.75, p = .19) was found. Contrary to H3b, participants perceived lower clarity of NS speech when NS used the Speech Speedometer (M=5.28, SE=.33) than when they used the control display (M=6.00, SE=.27).…”
Section: Effects Of Speech Speedometer On Nns Perception Of Ns Speech and Othermentioning
confidence: 99%
“…Previous work has explored methods for improving intercultural communication between native and non-native speakers. This includes efforts to reduce cognitive burden [39] and improve comprehension [40,41] for non-native speakers, and to establish conversational grounding in multilingual conversations [42][43][44]. For the most part, evaluations of these kinds of tools are based on how participants perform communication tasks in lab settings.…”
Section: Language Supportmentioning
confidence: 99%
“…Foreign students would benefit from tools that help them communicate their difficulties to host-nationals. With regard to language-difficulties, previous work has demonstrated that making native-speakers aware of non-native speakers' difficulties encouraged more effective communication strategies [42]. Additionally, language barriers tend to be asymmetric because, although native speakers are aware of non-native speakers' difficulties, they do not understand how this affect nonnative speakers' behavior [60].…”
Section: Communicating Problemsmentioning
confidence: 99%